Facilitating the Validation of Novel Protein Biomarkers for Dementia: An Optimal Workflow for the Development of Sandwich Immunoassays - del Campo, Marta; Jongbloed, Wesley; Twaalfhoven, Harry A. M.; Veerhuis, Robert; Blankenstein, Marinus A.; Teunissen, Charlotte E. (Frontiers in Neurology, 2015)
Different neurodegenerative disorders such as Alzheimer’s disease (AD) and frontotemporal dementia (FTD) lead to dementia syndromes. Dementia will pose a huge impact on society and thus it is essential to develop novel tools able to detect the earliest, most sensitive, discriminative and dynamic biomarkers for each of the disorders. To date, the most common assays used in large-scale protein biomarker analysis are enzyme-linked immunosorbent assays (ELISA), such as the sandwich immunoassays, which are sensitive, practical and easily implemented. However, due to the novelty of many candidate biomarkers identified during proteomics screening, such assays or the antibodies that specifically recognize the desired marker are often not available. The development and optimization of a new ELISA should be carried out with considerable caution since a poor planning can be costly, ineffective, time consuming and it may lead to a misinterpretation of the findings. Here we describe a specific and detailed workflow to develop and validate new ELISA for a successful and reliable validation of novel dementia biomarkers. The proposed workflow highlights the main issues in the development of an ELISA and covers several critical aspects including production, screening and selection of specific antibodies until optimal fine-tuning of the assay. Although these recommendations